TI_GERICHTE 12.2011.24 vom 18. Juli 2011 , Affitto agricolo. Contestazione disdetta. Richiesta di protrazione - TI Tribunale d'appello (2011)
Affitto agricolo. Contestazione disdetta. Richiesta di protrazione